2019
DOI: 10.1177/1557085119878268
|View full text |Cite
|
Sign up to set email alerts
|

It Depends on the Situation: Women’s Identity Transformation in Prison, Jail, and Substance Abuse Treatment Settings

Abstract: Scholars have examined women’s identity development in prisons. Less is known if and how identity development affects women in different stages of the correctional system. This study applies narrative identity theory, cognitive transformation theory, and literature on pains of imprisonment to 118 women’s life-story narratives to explore identity change in prisons, jails, and substance abuse treatment. Qualitative analysis revealed noteworthy situational differences in the prevalence and nature of identity tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 27 publications
(42 reference statements)
0
23
0
Order By: Relevance
“…According to this theory, individuals who have broken the law desist when they alter their routine activities to be more prosocial, and pinpointed employment as a key reason to alter former antisocial routines. Further, work using narrative identity theory has identified that justice-involved women value opportunities to construct prosocial identities (Hoskins & Cobbina, 2020), and that life narratives that incorporate prosocial activities produce positive effects for women (Morash et al, 2020). Consistent with the sentiments of the women in our sample, the time demands of prosocial activities such as work can improve well-being by dissuading women motivated to avoid crime from breaking the law.…”
Section: Discussionmentioning
confidence: 99%
“…According to this theory, individuals who have broken the law desist when they alter their routine activities to be more prosocial, and pinpointed employment as a key reason to alter former antisocial routines. Further, work using narrative identity theory has identified that justice-involved women value opportunities to construct prosocial identities (Hoskins & Cobbina, 2020), and that life narratives that incorporate prosocial activities produce positive effects for women (Morash et al, 2020). Consistent with the sentiments of the women in our sample, the time demands of prosocial activities such as work can improve well-being by dissuading women motivated to avoid crime from breaking the law.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, our findings should be interpreted with caution. It is important for future research to include interviews with incarcerated women to examine, in their own words, how they experience segregation, and how it affects their behaviors, mental health, relationships with other women, and identities while in prison (Hale, 2020; Hoskins & Cobbina, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…So, they're more like talking to me in a nice manner." According to Lysandra, officers "switched their whole perspective" and afforded her better treatment during the most recent raid because she successfully presented as a "good mother" (see also Hardesty & Black, 1999;Hoskins & Cobbina, 2020;Stearns, 2019). Conceptions of the "good mother" position women as caring nurturers readily available to care for their children, irrespective of circumstance (Collins, 2000;Kline, 1992;Krane & Davies, 2007; see also Dow, 2016).…”
Section: Motherhood and Household: Vulnerability And Resourcementioning
confidence: 99%